Policy transfer in criminal justice: crossing cultures, breaking barriers - McFarlane, Mary Anne (Palgrave Macmillan, 2014)
"Will 'what works' in one country work in another? This unique collection examines the cross-cultural transfer of skills and expertise, drawing out the opportunities and challenges involved in taking penal practices from one country to another.Focusing on an EU support project with Turkey's Ministry of Justice, the contributors evaluate their experiences of developing probation services and inter-agency programmes with juvenile offenders and victims of crime internationally. The volume highlights the need for strong communication and social skills to ensure mutual understanding, respect and sustainability, as well as underlining an awareness of historical, political, social, geographical, economic, religious and political factors as an essential precondition for successful cross-cultural transfer.Outlining a helpful set of recommendations for future projects, applicable to a range of sectors and to cross-cultural work in Europe and beyond, this collection will be a valuable resource to practitioners, especially those working with Muslim communities, as well as scholars in Criminal Justice, Social Work and Health Care"--